Propagation properties of Airy–Gaussian beams in centrosymmetric photorefractive media. Issue 19 (11th November 2018) - Jiang, Qichang; Su, Yanli; Ma, Ziwei; Zheng, Wei; Li, Yonghong; Nie, Hexian
ABSTRACT: Based on the biased centrosymmetric photorefractive media, we investigate numerically the propagation and interaction properties of Airy–Gaussian beams. The single Airy–Gaussian beam forms the one-component breather with the help of the photorefractive nonlinearity. The interaction properties of two Airy–Gaussian beams can be controlled by adjusting the relative parameters, such as photorefractive nonlinearity, transverse distance and relative phase of two incident beams. The two-component breather with ladder structure can be observed for both the in-phase and out-of-phase cases when the self-acceleration property is balanced by the photorefractive nonlinearity. The one- or three-component breathers can be observed for the in-phase case only when the transverse distance takes a certain range.